Algebra-Grundlagen-Brüche
$\text{Kürzen}$
1
2
3
4
5
6
7
8
9
10
11
12
13
$\frac{a}{b} - \frac{c}{d}$
1
2
3
4
5
6
7
8
9
10
$a\frac{b}{c}- d\frac{e}{f}$
1
2
3
4
5
6
7
Beispiel Nr: 01
$\begin{array}{l} \text{Gegeben:}\\
\text{Bruch1:}\frac{a}{b} \\
\text{Bruch2:}\frac{c}{d} \\
\\ \text{Gesucht:}
\\\text{Summe,Differenz,Produkt,Quotient}
\\ \frac{a}{b} - \frac{c}{d}\\ \textbf{Gegeben:} \\ a=3 \qquad b=4 \qquad c=5 \qquad d=6\\ \\ \textbf{Rechnung:} \\
\text{Hauptnenner: kgV( }4,6 \text{) }= 12 \\
\text{Erweiterungsfaktoren: }\frac{12}{4}=3 \qquad \frac{12}{6}=2 \\
\\\text{Summe}\\
\frac{3}{4}+\frac{5}{6}=\frac{3\cdot3}{4\cdot3}+\frac{5\cdot2}{6\cdot2}= \frac{9+10}{12}=\frac{19}{12}=1\frac{7}{12} \\
\\\text{Differenz}\\ \frac{3}{4}-\frac{5}{6}=\frac{3\cdot3}{4\cdot3}-\frac{5\cdot2}{6\cdot2}= \frac{9-10}{12}=\frac{-1}{12}=-\frac{1}{12} \\
\\\text{Produkt} \\ \frac{3}{4} \cdot \frac{5}{6}=\frac{3\cdot5}{4\cdot6}= \frac{15}{24}=\frac{5}{8} \\
\\\text{Quotient} \\ \frac{3}{4} : \frac{5}{6}=\frac{3}{4} \cdot \frac{6}{5}= \frac{18}{20}=\frac{9}{10} \\
\end{array}$